Potensi Briket Arang Berbahan Sekam Sebagai Energi Alternatif - Noviyarsi Noviyarsi; Dessi Mufti; Fuji Kurniawan Jafri (UIN Sultan Syarif Kasim Riau, 2015)
Nowadays, it’s time to focus on renewable energy because of decreased in oil, charcoal and gas production. One of renewable energy to substituted oil and gas is briquette by using paddy husk as material. Potential of paddy husk which produced from rice milling is about 20-30%, bran about 8-12% and rice about 50-63.5%. The purpose of this research was to analyzed potential of husk charcoal briquette as renewable energy. This research method was experiment. Pyrolysis process has been done using conventional pyrolysis tool. Adhesive used to make briquette was adhesive starch which composition of starch and water was 1:16. Composition of husk charcoal and starch was tested in 2 compositions that are 1:8% and 1:10%. Result of caloric value show that briquette with composition 1:8% gave the highest caloric value about 5.580,19 kal/gr. It means that this value fulfill SNI standard with minimum caloric value was 5.000 kal/gr.Keywords: charcoal briquette, paddy husk, renewable energy.